A Careerography of John F. Kennedy Jr. (February 2021) - Bigony, Cara; Alpers, Anne; Ponterotto, Joseph G.
This article presents a careerography of John F. Kennedy Jr. (JFK Jr.), a late 20th-century iconic personality. Careerography adapts psychobiography by anchoring its interpretive lens in established theories of career development. In our longitudinal case study of JFK Jr., the theories of Donald Super and Mary Sue Richardson served as the career theories to frame and interpret his career development. The sequential model of careerography applied to JFK Jr. focused on (1) our selection of the historical subject, (2) ethical considerations and bracketing, (3) outlining initial research questions, (4) choosing anchoring career theories, (5) engaging the iterative research and theory application process, and (6) writing the careerography. The article concludes with a brief discussion of how careerography adds to the historical study of notable personalities, and how in turn career theory can be informed through the intensive case study method of careerography.